CAPTURING CHANGES OVER TIME IN LONGER LIVES IN THE LONG LIFE FAMILY STUDY. (11th November 2018) - Perls, T T; Raghavachari, N
Abstract: Since 2006, the LLFS has followed 550 families consisting of older and offspring generations and spouses (n=5, 050) demonstrating familial clustering for exceptional longevity. Probands are/were from the Pittsburgh, Manhattan and Boston areas and Denmark. Two in-person visits were performed 8 years apart in 2006–2008 and 2015–2017 collecting detailed sociodemographic, medical, cognitive and physical and lung function data, and blood for storage, biomarkers, RNA and DNA. Every year, subjects are assessed by phone/mail for changes in multiple domains. In this symposium we highlight the advantages in the LLFS of measuring changes over time. We describe here pulmonary functions (PF) changes over time and the increased power such changes afford us over cross-sectional measures in discovering genetic variants associated with PF. Measuring incident dependence reveals that a substantial proportion of older generation survivors (69%) have remained independent over a 7 year period, in-part supporting further investigation of factors underlying preserved function at extreme ages. Integrative analysis can be used to group multiple different factors including genetic and non-genetic molecular biomarkers and physical measures to predict rates of decline in multiple cognitive function domains. Similarly, "distance measure" can be used to construct composite measures of physiological dysregulation based on multiple biomarkers measured cross-sectionally and even better, over time, to predict for example, mortality. The LLFS is now exploring the utility of enrolling the grandchild generation and following these subjects over time. In both Danish children and grandchildren generations, we demonstrated substantial lower mortality and risk of hospitalization for virtually all disease groups.